Time trends in Alzheimer’s disease mortality attributable to metabolic risks and smoking in China from 1990 to 2019: an age-period-cohort analysis - Sun, Simeng; Zhang, Ting; Yu, Hao; Xia, Ting; Yao, Yunan; Sun, Mengting; Liang, Hongmei; Huang, Qiaoyu; Wang, Weiwei; Yang, Huafeng; Hong, Xin (Frontiers in Aging Neuroscience, 2024)
Background: With the increase in the aging population worldwide, Alzheimer's disease has become a rapidly increasing public health concern. In the Global Burden of Disease Study 2019 (GBD 2019), there are three risk factors judged to have evidence for a causal link to Alzheimer's disease and other dementias: smoking, high body-mass index (HBMI), and high fasting plasma glucose (HFPG). Objective: This study aimed to analyze trends in AD mortality and the relevant burden across China from 1990 to 2019, as well as their correlation with age, period, and birth cohort. Methods: The data were extracted from the GBD 2019. Trends in AD mortality attributable to metabolic risks (HFPG and HBMI) and smoking were analyzed using Joinpoint regression. The age-period-cohort (APC) model was used to evaluate cohort and period effects. Results: From 1990 to 2019, the overall age-standardized mortality rate of AD increased, especially in women. There was an increase in AD mortality due to smoking in the net drift, and it was more significant in women (0.46, 95%CI=[0.09, 0.82]) than men(-0.03, 95%CI=[-0.11, 0.05]). For the cause of HFPG, the net drift values for men and women were 0.82% and 0.43%. For HBMI, the values were 3.14% and 2.76%, respectively, reflecting substantial increases in AD mortality. Conclusions: Time trends in AD mortality caused by metabolic risks and smoking in China from 1990 to 2019 have consistently increased. Therefore, it is necessary to prevent excessive weight gain and obesity during the later stages of life, especially for females.